Emerging low-molecular weight nucleopeptide-based hydrogels: state of the art, applications, challenges and perspectives. Issue 13 (23rd March 2022) - Giraud, Tristan; Hoschtettler, Paul; Pickaert, Guillaume; Averlant-Petit, Marie-Christine; Stefan, Loic
Abstract : This minireview highlights the interests, high potential, applications and perspectives of the emerging low-molecular weight nucleopeptide-based hydrogels. Abstract : Over the last twenty years, low-molecular weight gelators and, in particular, peptide-based hydrogels, have drawn great attention from scientists thanks to both their inherent advantages in terms of properties and their high modularity ( e.g., number and nature of the amino acids). These supramolecular hydrogels originate from specific peptide self-assembly processes that can be driven, modulated and optimized via specific chemical modifications brought to the peptide sequence. Among them, the incorporation of nucleobases, another class of biomolecules well-known for their abilities to self-assemble, has recently appeared as a new promising and burgeoning approach to finely design supramolecular hydrogels. In this minireview, we would like to highlight the interest, high potential, applications and perspectives of these innovative and emerging low-molecular weight nucleopeptide-based hydrogels.